Optimal and automated decentralised converter control design in more electrical aircraft power electronics embedded grids. Issue 3 (10th January 2021) - Dewar, D.; Formentini, A.; Li, K.; Zanchetta, P.; Wheeler, P.
Abstract: In modern power systems, the proliferation of power electronics converters, and distributed generation raises important issues concerning inter‐connected switching units in terms of performance, stability and robustness. Such phenomenon are more prominent in micro‐grids, such as modern local low voltage distribution systems, more electric aircraft power systems etc., where many power converters are connected to the same non‐stiff low power ac grid, and strongly interact with each other. Locally designed converter control systems on the same electrical bus exhibit interactive behaviour. If not taken properly into account, external disturbances to the system at given operating conditions may result in the degradation of performance, failure to meet operating conditions and, in some cases, instability. This paper presents a new approach to synthesise converter controllers in more electric aircraft ac distribution grids (which is, however, applicable to all power electronics embedded systems), keeping in consideration dynamic interactions among subsystems. An optimal control design approach based on H 2 optimisation is therefore proposed. Phase‐locked loops have also been considered, and their tuning has been included in the general tuning procedure of the whole system. Simulation, and experimental results show good improvements in terms of dynamic performance, and interaction mitigation.